The Nature of Asian Politics - Gilley, Bruce (Cambridge : Cambridge University Press, 2014)
The Nature of Asian Politics is a broad and thematic treatment of the fundamental factors that characterize politics in the fourteen key countries of Southeast and Northeast Asia. Bruce Gilley begins with an overview of state-society relations, then moves on to the fundamental questions of development and democracy, and finally shifts to an exploration of governance and public policy in the region. This book proposes an Asian governance model that is useful for understanding politics from Japan to Indonesia. By reviving an earlier paradigm known as oriental despotism and applying it to political theories on the Asian region, this book is likely to attract wide debate among students of Asian politics and among Western policy makers seeking to engage the region.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).